Blowing Away the Pain: A Technique for Pediatric Pain Management. Issue 6 (November 2014) - Jacobs, Adrian; Price, Harper N.; Popenhagen, Mark P.
Abstract Painful medical procedures in childhood may have long‐term negative effects on development and future tolerance of pain. We describe a distraction technique for pediatric pain management that involves "blowing away the pain." This technique may be used for acute pediatric procedures as well as for patients with chronic pain.